2008
DOI: 10.1002/sd.383
|View full text |Cite
|
Sign up to set email alerts
|

Is air transport an effective tool for sustainable development?

Abstract: Several authoritative studies indicate that air transport makes a strong, positive contribution to economic development - a contribution that far outweighs the environmental and social costs of aviation. This article investigates this benign view, analysing the assumptions upon which it is based and arguing that the relationship between air transport and economic benefits may be more complex than is commonly held. In particular, the benefits of air transport services may be highly unevenly distributed, with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Recent research suggesting that the relationship between the aviation sector and economic development is not straightforward and the economic benefi ts of aviation are somewhat unevenly distributed (Daley, 2008) may perpetuate this situation. Thus the outcomes of deliberative processes associated with a more refl exive ecological modernization may be uncertain (Morse, 2008) and may not achieve requisite discursive closure for sustainable aviation policy to function properly.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research suggesting that the relationship between the aviation sector and economic development is not straightforward and the economic benefi ts of aviation are somewhat unevenly distributed (Daley, 2008) may perpetuate this situation. Thus the outcomes of deliberative processes associated with a more refl exive ecological modernization may be uncertain (Morse, 2008) and may not achieve requisite discursive closure for sustainable aviation policy to function properly.…”
Section: Discussionmentioning
confidence: 98%
“…Daley (2009) takes a different approach by focusing on the relationship between economic benefits and aviation. Such benefits are definitely there.…”
Section: Current Understanding Of Sustainable Airportsmentioning
confidence: 99%
“…Numerous studies have shown that air transportation makes a significant contribution to a country's economic and social development and represents an important engine of economic growth for nations. Daley (2009) summarizes the economic benefits of aviation, finding that it allows companies to expand and penetrate other markets, it contributes to corporate specialization by generating scale economies and stimulating direct foreign investment, and there are also social benefits in terms of workforce mobility, leisure travel and cultural exchanges, amongst others.…”
Section: Introductionmentioning
confidence: 99%